Pemanfaatan Sampah Plastik menjadi Ecobrick dalam Program KKN UNP di Sijantang Koto - Yummi Meirafoni; Intan Ramadhani; Meuthia Sandy Degita; Nadya Meriden Guci; Abdul Hamid Gusri; Yunita Hanifa (CV. ITTC INDONESIA, 2025)
The problem of plastic waste is an increasingly pressing environmental issue due to its difficult-to-decompose nature and its negative impact on environmental quality and community settlements. Sijantang Koto Village in Sawahlunto City faces a similar problem, where household plastic waste is still often disposed of carelessly or burned due to limited waste management. This community service activity, conducted through the Community Service Program (KKN) of Padang State University (UNP), aims to reduce the volume of plastic waste, increase community participation in waste management, and support the creation of inclusive, safe, resilient, and sustainable settlements. The method used is direct action with a participatory approach through collecting and compacting plastic waste into used bottles to create ecobricks. The results of the activity indicate that the resulting ecobricks can be used as elements of the village environment. This activity contributes to the achievement of the Sustainable Development Goals (SDGs), specifically Goal 11 on inclusive, safe, resilient, and sustainable settlements and Goal 12 on responsible consumption and production.